Digital Transformation and MSME Competitiveness: Examining the Mediating Effect of Innovation Management (A PLS-SEM Study in Indonesian MSMEs) - Selfiyan Selfiyan; Eso Hernawan; Etty Herijawati (Indonesian Journal of Islamic Economics and Finance, 2026)
Digital transformation has become a strategic necessity for Micro, Small, and Medium Enterprises (MSMEs), particularly in emerging economies where firms face resource and managerial limitations. This study examines the influence of Information Technology Capability, Innovation Orientation, and Managerial Capability on MSME competitiveness, with Innovation Management as a mediating variable. Using a quantitative approach, data were collected from 400 MSME owners and managers in the Pasar Lama area of Tangerang City and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that organizational capabilities significantly influence both Innovation Management and MSME competitiveness. Innovation Management was found to be the strongest predictor of competitiveness and played a significant mediating role in the relationship between organizational capabilities and competitiveness. These results suggest that sustainable competitiveness in MSMEs depends not only on digital technology adoption but also on the ability to effectively manage innovation processes. This study contributes to the understanding of how innovation management strengthens MSME competitiveness during digital transformation in emerging economy contexts.